2018
DOI: 10.4103/ijoy.ijoy_61_17
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a structured yoga program on fatigue, depression, cardiorespiratory fitness, and quality of life in a postmenopausal breast cancer survivor

Abstract: A 52-year-old postmenopausal female diagnosed with duct carcinoma of the left breast underwent modified radical mastectomy 2 years ago. She had completed six cycles of chemotherapy postsurgery and complained of significant fatigue and depression. Her fatigue score on Piper Fatigue Scale was 4.1 and depression score on Beck's Depression Inventory was 22. She had a poor 6-min walking distance and a reduced quality of life. She was given a structured yoga program for 40 min five times a week for 4 weeks. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…After treatment, it is important to control gastric cancer survivors' symptoms in order to enable their adaptation to their new life and improve their QoL. In this regard, intervention programs such as complex exercise therapy and health education therapy, which have been determined to produce successful result with other type of cancer survivors, may be effective [9,32]. In terms of education methods, the conventional method based on brochures and multimedia can be used to provide basic knowledge in only a limited way [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After treatment, it is important to control gastric cancer survivors' symptoms in order to enable their adaptation to their new life and improve their QoL. In this regard, intervention programs such as complex exercise therapy and health education therapy, which have been determined to produce successful result with other type of cancer survivors, may be effective [9,32]. In terms of education methods, the conventional method based on brochures and multimedia can be used to provide basic knowledge in only a limited way [8].…”
Section: Discussionmentioning
confidence: 99%
“…Most studies on cancer survivors have been conducted on survivors of breast cancer and childhood cancer [8][9][10][11]. Even in South Korea, there has not been much research on gastric cancer survivors despite the high occurrence rate of this cancer and high survival rate of individuals with this cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies have shown a high frequency of cardiovascular side effects after breast cancer treatment [3,4]. This circumstance leads to a variety of interventions designed to improve the quality of life of patients with breast cancer [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Physical activity is increasingly recognized as an effective method of reducing emotional distress and improving life quality among patients who survived cancer. A growing body of research indicates the benefits of yoga exercises [8][9][10][11][12][13][14], cognitive behavioural therapy [15], mindfulness-based stress reduction [16,17], physical activity [18], music therapy [19,20], progressive muscular relaxation [21][22], and mixed aerobic and muscle strengthening exercise [23] for improving mental and physical conditions in breast cancer patients.…”
Section: Introductionmentioning
confidence: 99%